2000
DOI: 10.1080/07391102.2000.10506671
|View full text |Cite
|
Sign up to set email alerts
|

A Molecular Dynamics Simulation Study of Coaxial Stacking in RNA

Abstract: We report on unrestrained molecular dynamics simulations of an RNA tetramer binding to a tetra-nucleotide overhang at the 5'-end of an RNA hairpin (nicked structure) and of the corresponding continuous hairpin with Na+ as counterions. The simulations lead to stable structures and in this way a structural model for the coaxially stacked RNA hairpin is generated. The stacking interface in the coaxially stacked nicked hairpin structure is characterized by a reduced twist and shift and a slightly increased propell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Simulations involving RNA are accumulating rapidly, although the size, charge, and structural variety of these molecules continue to pose significant challenges. Several studies have addressed the dynamics of the basic motifs found in folded RNA, including mispairs such as flexible water-bridged UC pairs, or coaxial stacking, where the absence of backbone continuity causes kinking and untwisting but does not enhance flexibility . Studies of stem loops show that nanosecond dynamics maintain stable conformations but cannot sample extensively enough to identify conformational substates .…”
Section: Rna and Rna Complexesmentioning
confidence: 99%
“…Simulations involving RNA are accumulating rapidly, although the size, charge, and structural variety of these molecules continue to pose significant challenges. Several studies have addressed the dynamics of the basic motifs found in folded RNA, including mispairs such as flexible water-bridged UC pairs, or coaxial stacking, where the absence of backbone continuity causes kinking and untwisting but does not enhance flexibility . Studies of stem loops show that nanosecond dynamics maintain stable conformations but cannot sample extensively enough to identify conformational substates .…”
Section: Rna and Rna Complexesmentioning
confidence: 99%
“…X-ray crystallography, solution experiments, and simulations have distinct areas of application and provide complementary views on the structure and dynamics of K-turns. Although limited by force field approximations and the timescale of the simulations, MD is capable of providing qualitative insights into RNA structure and dynamics (Auffinger et al, 1999(Auffinger et al, , 2004Westhof, 1998, 2000;Beveridge and McConnell, 2000;Cheatham and Kollman, 1997;Csaszar et al, 2001;Giudice and Lavery, 2002;Guo et al, 2000;Guo and Gmeiner, 2001;Hermann et al, 1998;Nagan et al, 1999Nagan et al, , 2000Norberg and Nilsson, 2002;Razga et al, 2004;Reblova et al, 2003aReblova et al, ,b, 2004Sanbonmatsu and Joseph, 2003;Sarzynska et al, 2000;Schneider et al, 2001;Schneider and Suhnel, 2000;Stagg et al, 2003;Williams and Hall, 2000;Zacharias, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Besides the experimental approaches, molecular interactions in RNA molecules can be studied by a variety of advanced molecular modeling tools Westhof, 1998, 2001;Beveridge and McConnell, 2000;Brandl et al, 2000;Cheatham and Kollman, 2000;Cheatham and Young, 2000;Chin et al, 1999;Guo et al, 2000;Hermann et al, 1997;Lahiri and Nilsson, 2000;Nagan et al, 1999Nagan et al, , 2000Sarzynska et al, 2000;Schneider and Suhnel, 2000;Schneider et al, 2001;Sponer et al, 2001;Williams and Hall, 1999;Zacharias, 2000). This reflects the enormous progress of computer hardware and software in the last decade, during which the actual performance of computers increased by at least three orders of magnitude.…”
Section: Introductionmentioning
confidence: 99%